An Analysis Of Students' Ability In Writing DescriptiveText At Etp's Students Of Accounting Education - Putri, Arditasari; , Drs. Agus Wijayanto, Ph.D (2017)
This research focuses on students' ability in writing descriptive text, the development of main idea, the students' grammatical aspects, and cohesion and coherence at ETP's students of accounting education in Muhammadiyah University of Surakarta. The type of this research is qualitative research. The data source is the task to write descriptive paragraphs by ETP's students and giving information from informants or tutor who teaching the students. The researcher collects the data by giving assignments to students to write descriptive text. The techniques for analyzing data are reading the students' writing of descriptive text, analyzing the aspects of descriptive text; the development of main idea, grammatical aspects of writing, cohesion and coherence. The researcher classifying and scoring the students test of writing descriptive paragraph, and drawing conclusion based on the result of the research of the students' ability in writing descriptive text. The results show that (1) there are six techniques of developing the paragraph in students' descriptive texts, i.e. classification, deductive pattern, giving facts, objective pattern, subjective pattern, and storytelling. The highest percentage that is using deductive pattern with 29.8%, the second technique frequently used is giving the facts with 28.6%. The third frequently used is storytelling with 19%. The fourth frequently used is subjective pattern with 13%. Furthermore is the using of objective pattern with 6%. And the last is classification technique with 3.6%. (2) There are four types of error found in students writing; addition, misformation, misordering, and omission. The grammar errors which often appear are misformation error with 37%. Second, the frequent error made by the students is omission error with 29%. Furthermore, there is addition error with 19%. And the last is misordering error with 15%. (3) Cohesion aspects that in students descriptive text are seven types of conjunction, namely "although", "and", "because", "but", "however", "so", and "then". The use of conjunction mostly used is "because" with 34.7%, then the second is word "but" with 27%. The third frequent is conjunction "and" with 23.1%. Furthermore is the use of conjunction "although", "however", "so", and "then" with 3.8%.